The Role of Technical and Self Skills in Improving Competitiveness A field study on public banks in Lattakia Governorate - Mia, Ali; Makhos, Dima; Nasser, Hussein (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Leadership skills are one of the most important skills that managers must have in organizations because of their importance in improving performance and guiding it in the direction that ensures achieving the overall goals in the optimal way. Numerous can be summed up in the self, technical, intellectual and human skills, as these skills contribute to improving the competitiveness of organizations, and strengthening their competitive position in the market. The research aims to assess the availability of technical and subjective skills among a sample of managers of public banks in Lattakia, and to study their relationship to competitiveness in terms of size of competitiveness and scope of competition. To achieve this, two main hypotheses were formulated, and the researcher used the interview method to collect data that was analyzed using statistical tests, the most important of which are: One-Sample T. test, and Pearson Correlation. The researcher reached several results, the most important of which are: a good direct relationship between technical skills and competitiveness, and an intermediate positive relationship between subjective skills and competitiveness. تعد المهارات القيادية من أهم المهارات التي يجب أن تتوافر لدى المدراء في المنظمات نظراً لأهميتها في تحسين الأداء وتوجيهه بالاتجاه الذي يضمن تحقيق الأهداف العامة بالشكل الأمثل، وتستمد أهميتها من أهمية المورد البشري كونه المورد الأكثر أهمية وتأثيراً في أداء المنظمة، حيث قسم الباحثون هذه المهارات تقسيمات عديدة يمكن إجمالها بالمهارات الذاتية والفنية والفكرية والإنسانية، حيث أن هذه المهارات تسهم في تحسين القدرة التنافسية للمنظمات، وتدعيم مركزها التنافسي في السوق. ويهدف البحث إلى تقييم مدى توافر المهارات الفنية والذاتية لدى عينة من مدراء المصارف العامة في محافظة اللاذقية، ودراسة علاقتها بالقدرة التنافسية من حيث حجم القدرة التنافسية ونطاق التنافس. ولتحقيق ذلك تمّ صياغة فرضيتين رئيستين، واستخدم الباحث أسلوب المقابلة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample T. test، واختبار الارتباط الثّنائي Pearson Correlation. وقد توصل الباحث إلى عدّة نتائج أهمّها: وجود علاقة طردية جيدة بين المهارات الفنية والقدرة التنافسية، وعلاقة طردية متوسطة بين المهارات الذاتية والقدرة التنافسية.